Strategi Pengembangan Wilayah Dalam Meningkatkan Pertumbuhan Ekonomi Masyarakat di Kecamatan Karang Tanjung Pandeglang - Fikri Hariadi; Muhammad Afandi Siddiq; Akrom Akrom (PT. Saha Kreasi Indonesia, 2026)
This study analyzes regional development strategies in improving community economic growth in Karang Tanjung District, Pandeglang Regency. With an area of 19.07 square kilometers and a population density of 1,805 people per square kilometer, this district has superior potential in the trade sector and small and medium food processing enterprises with more than 250 business units. However, data shows the poverty rate reaches 12.5 percent, access to formal capital is only 8-10 percent, digital technology adoption is below 15 percent, damaged roads span 11 kilometers, clean water coverage is only 65 percent, and stunting prevalence is 18.5 percent. The research method uses a descriptive qualitative approach with secondary data analysis from the Central Bureau of Statistics and regional planning documents. The results formulate five main strategies: strengthening UMKM clusters, establishing a Sub-district Microfinance Institution, business digitalization through digital posts in each village, priority infrastructure improvement, and continuous training and assistance. This research is expected to serve as policy consideration for the Pandeglang Regency Government in formulating development planning that supports community economic empowerment.